Selective activation of TCR gamma delta +ve cells in endemic Burkitt's lymphoma - Futagbi, G.; Welbeck, J.E.; Tetteh, J.K.A.; Hviid, L.; Akanmori, B.D. (My University, 2007)
Abstract Background The overlap in geographical distribution of Plasmodium falciparum malaria and endemic Burkitt's lymphoma (eBL) – an aggressive Epstein-Barr virus (EBV)-associated B-cell tumour occurring almost exclusively in the tropics – strongly suggests a link between the two diseases. It is suspected that the polyclonal B-cell activation in P. falciparum malaria may precipitate a breakdown in homeostatic T-cell control of EBV-immortalized B-cell proliferation. Previous studies have suggested that a particular T-cell subset, characterized by expression of Vδ1+ γδ T-cell receptors, is important for maintaining B-cell homeostasis, both in P. falciparum- exposed populations and in individuals subject to polyclonal B-cell activation of other aetiology. The objective of the present study was, therefore, to characterize lymphocyte phenotypes and to investigate possible differences in T-cell subset composition and activation status in P. falciparum-exposed Ghanaian children with and without eBL. Methods Venous blood samples in heparin from 21 eBL patients (mean age: 7.0 years; range: 3–11 years), referred to the Burkitt's Tumour Centre at Korle-Bu Teaching Hospital, Accra and 15 healthy, age and sex matched children, were stained with fluorescein isothiocyanate (FITC)-, phycoerythrin (PE)-, R-phycoerythrin (RPE)- and RPE-Cy5-conjugated antibodies (CD3, CD4, CD8, CD25, CD69, CD95, HLA-DR, TCR-γδ, Vδ1, Vδ3, Vγ9 and B-cells) and acquired on a flow cytometer. Results A reduction in the proportion of CD3+ cells in eBL patients, due mainly to perturbations among TCR-γδ+ cells was observed. In contrast, the proportions of CD4+ or CD8+ cells were relatively unaffected, as were the mean numbers of peripheral blood mononuclear cells. Conclusion Selective changes in numbers and activation status of TCR-γδ+ cells occurs in Ghanaian children with eBL, a pattern which is similar to P. falciparum-induced changes. The data supports the hypothesis of a regulatory role for Vδ1+ TcR-γδ T-cells in maintaining B-cell homeostasis and provides insights into the pathogenesis of eBL.